Synthesis of Substituted Thioureas and Their Sulfur Heterocyclic Systems of p-Amino Salicylic Acid as Antimycobacterial Agents - Mohammed Saleh I. T. Makki; Reda M. Abdel-Rahman; Hassan M. Faidallah; Khalid Ali Khan (Journal of Chemistry)
A series of new N,N′-substituted thioureas (2, 6, and 8) and their sulfur heterocycles as thiobarbituric acids (3, 4, and 7), 2-thioxothiazoliodin-4-one (10), thiazolidin-4-one (11), 1,2,4-triazol-5-thione (14), and 1,3,4-thiadiazole (15) of p-Amino salicylic acid (PAS) have been synthesized from treatment with dithiocarbazinate (1, 5 and 12) followed by heterocyclization with dimethyl malonate, chloroacetic acid, and/or trifluoroacetic anhydride. The structures of the newly synthesized compounds were substantiated with IR, H1, and C13 NMR spectral data and elementary microanalyses. The in vitro antitubercular activity of synthesized compounds against M. tuberculosis strain H37Rv showed moderate-to-good activity.